Model Perilaku Pemodal terhadap Risiko dan Jenis Investasi pada Sektor Perbankan (Studi Perilaku Keuangan Berbasis Psikologi) - Rr. Iramani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The purpose of this research is to examine psychological factor as predictors investor’s investment risk and the type of investments selected. To test the hypothesis proposed in this research used Binary Logistic.The results of this research show that the status quo and emotional factors can be used to predict the behavior of investors. Meanwhile, the security factor in investing, and the status quo factor can be used to predict the selected type of investment.Keywords: Behavior Finance, Psychological Factors, Risk Seeker, Risk Averter, Investment types.